Assessing the Resilience of Rural Settlements in Mahneshan Township Against Food Insecurity in Drought Conditions - Masumeh Mohammadlo; Abdolreza Rahmani Fazli; Jila Sajjadi; Mehdi Cheraghi (مدیریت بیابان)
One of the significant consequences of reduced resilience in human settlements, driven by climate change and drought, is the rise in food insecurity. The counties within Zanjan Province face varying degrees of drought severity. This study aims to evaluate the resilience of rural settlements to food insecurity under drought conditions. The research is applied in nature and adopts a descriptive-analytical approach. The statistical population comprises 122 inhabited villages, with a sample size of 30 villages from Mahneshan County. Data collection was carried out through library research and field observations, while data analysis was performed using spatial analysis tools within the GeoDa software. An assessment of the Standardized Precipitation Index (SPI) revealed that the study area experienced seven mild wet years, seven mild droughts, and three moderate droughts. To investigate and measure food insecurity levels, raw data from the Household Income and Expenditure Survey of rural households, conducted by the Statistical Center of Iran from 2006 to 2022, were used to calculate the food insecurity index. The findings indicated that the average food insecurity index was 44.7%.The lowest and highest levels were observed in the villages of Yousefabad (23.4%) and Ebrahimabad (79.3%), respectively. Furthermore, the results showed that, among economic resilience indicators, dependency ratio, employment rate, and economic participation had the most significant influence on resilience. Among social resilience indicators, gender ratio, population growth (1995–2045), and male literacy rate were key factors. In terms of environmental-physical indicators, the percentage of retrofitted housing, the proportion of unauthorized wells, and the percentage of authorized agriculturalwells had the greatest impact on enhancing village resilience to drought and reducing vulnerability to food insecurity. It is crucial for planners to prioritize these indicators to enhance resilience and mitigate food insecurity in rural areas. These regions, due to their heavy reliance on natural resources and agriculture, are particularly vulnerable to the adverse effects of climate change and drought. Increased food insecurity can lead to migration, diminished economic and social welfare, greater pressure on limited resources, and, ultimately, a threat to the sustainability of rural settlements.